Sintesis Analog 3-0-Benzylstentorin sebagai Prekursor untuk Kerangka Dasar Blepharismin - TENI ERNAWATI; YOSHINOSUKE USUKI; HIDEO IIO (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
A Method for the synthesis of precursor for the basic skeleton of blepharismin and structural analog was described. Such compound is identified as potential drug for the treatment of antiviral and photodynamic therapy. Benzyl stentorin analog as the basic skeleton of blepharismin was effectively synthesized via reaction one of hydroxyl groups in bianthraquinone derivative with p-methoxybenzylchloride in the presence of potassium carbonate as base. Dimerization of bromo anthraquinone derivative produced dimmer in 55% while the formation of compounds analogous of 3-0-benzylstentorin resulted in 70% yield.